ODONTOMA: DIAGNOSTIC STRATEGIES IN DENTAL PRACTICE - Lopez, Andres Santiago Quizhpi; de Oliveira, Luiz Eduardo Prestes; Carvalho, Camila Nunes; de Siqueira, Rafael Rodrigues; de Souza, Geovanna Maria Ramos Porto; Afonso, Lauriney Santiago; da Silva, Leandro Stefanini; Souza Neto, Vicente Felizardo; Santos, Matheus Prates; Prates, Bruna Queiroz da Silva; Ribeiro, Clarissa Machado; da Costa, Rayane Perestrelo (Seven Editora, 2026)
Odontomas are the most common benign odontogenic tumors, classified by the World Health Organization (WHO) as compound or complex hamartomas. This narrative review analyzes contemporary evidence on diagnostic strategies in dental practice. Although generally asymptomatic and detected incidentally, these lesions severely impact dental development, causing retention of deciduous teeth and impaction of permanent teeth. Diagnosis is based on the association between clinical findings and imaging exams, highlighting Cone Beam Computed Tomography (CBCT) as a superior tool to conventional radiography because it allows three-dimensional visualization and precise surgical planning. The study discusses histopathology as a confirmatory step and the importance of differential diagnosis with osteomas and cementoblastomas. It concludes that early detection, combined with an interdisciplinary approach between surgery, orthodontics, and pathology, is essential to prevent root resorption and ensure predictable clinical results through conservative surgical enucleation.DOI: https://doi.org/10.56238/sevened2026.003-003